What was Killing Babies in Palma, Spain? Analysing Infant Mortality Patterns Using Individual-Level Cause of Death Data, 1836–1930 - Pujadas-Mora, Joana Maria (Historical Life Course Studies, 2024)
This paper explores infant mortality patterns to determine the epidemiological profile of the port city of Palma, Spain between 1836 and 1930 using individual-level cause of death and testing the newly constructed ICD10h coding system. Throughout the 19th century, infant mortality was well below 150 per 1,000 live births, possibly related to the practice of extended breastfeeding and frequent vaccination campaigns. However, between 1840 and 1860, as in other Spanish and European cities, the situation deteriorated. From the 1890s to 1930, the rate was almost always below 100. Post-neonatal mortality was higher than neonatal mortality, and the two rates began to fall at different times: the former in the 1870s and the latter in the 1920s. The main causes of neonatal mortality were congenital and birth disorders, while for post-neonatal mortality they were infectious diseases, mainly airborne, followed by waterborne and foodborne diseases. The decline in these rates was influenced by several factors, including improvements to public hygiene and nutrition and the quantity and quality of water sources. With regard to sex, a more pronounced female advantage was observed in post-neonatal mortality than in neonatal mortality. The seasonality of neonatal mortality in the 19th century was characterised by two peaks in autumn and winter, possibly related to the seasonality of births. In the 20th century, a summer peak was also observed. Post-neonatal mortality showed a sharp peak in summer, which receded and gave way to a winter peak by the late 1880s.